Are the stool characteristics of preterm infants affected by infant formulas? - Duman, Nuray; Utkutan, Selvinaz; Özkan, Hasan; Özdoğan, Şebnem (The Turkish Journal of Pediatrics, 2000)
The aim of this study was to investigate the relationship between the type of formula consumed and the stool characteristics and gastrointestinal symptoms of preterm infants prospectively. Seventy-five preterm infants weighing < 2000 g in our neonatal intensive care unit (NICU) were investigated. Four groups of 15 each were fed one of four commercial formula preparations (Prematil, Nenatal, Humana-0 and S-26) and the fifth group was breast-fed in a prospective, randomized, double-blind study. The stool characteristics and gastrointestinal problems were recorded daily from the first day till the time they were discharged by the nurses of NICU. No significant differences of daily weight gain was observed between the groups. No significant difference was observed in daily frequency of stool, distention, vomiting and gas passage between the groups during the enteral+parenteral and full-enteral nutrition periods. The infants fed by Prematil during the enteral+parenteral nutrition period had a higher percentage of hard stool occurrence than infants receiving Humana-0 and breast milk. In the full-enteral nutrition period, infants receiving Prematil had a higher percentage of hard stool occurrence than all the other groups, whereas breast-fed infants had a lower percentage of hard stool than all the other groups. While the group fed with Humana-0 had a higher percentage of green stool occurrence in the enteral+parenteral nutrition period, no significant difference was observed in the full-enteral nutrition period. In the enteral+parenteral nutrition period no additional therapy affected stool characteristics or the gastrointestinal system except in the case of the infant receiving phototherapy for whom the daily number of detections was significantly high. In this study, it was shown that the color and consistency of stool in preterm infant differs according to the preterm infant formulas, but no differences were observed in the frequency of defecation or in gastrointestinal system problems. When the infant formulas were compared with breast milk, it was shown that they cause a higher percentage of hard stool occurrence. An increased number of formula feedings are necessary to obtain a similar daily weight gain, but the color and the frequency of the stool and the gastrointestinal system problems were similar for breast-fed and formula-fed infants.
Keywords: breast feeding; infant formulas; stool characteristics